Nanoparticle impacts show high-ionic-strength citrate avoids aggregation of silver nanoparticles - Lees, J; Ellison, J; Batchelor-Mcauley, C; Tschulik, K; Damm, C; Omanovic̈, D; Compton, R (2013)
Quantitative analytical detection and sizing of silver nanoparticles is achieved by applying the new electrochemical method nanoparticle coulometry. For the first time, tri-sodium citrate is used as both an electrolyte and a nanoparticle stabilizing agent, allowing the individual particles to be addressed. © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.